2006
DOI: 10.1182/blood-2005-11-011775
|View full text |Cite
|
Sign up to set email alerts
|

Activation of αIIbβ3 is a sufficient but also an imperative prerequisite for activation of α2β1 on platelets

Abstract: Platelet integrins ␣ 2 ␤ 1 and ␣ IIb ␤ 3 play critical roles in platelet adhesion and thrombus formation after vascular injury. On resting platelets, both integrins are in a low-affinity state. However, agonist stimulation results in conformational changes that enable ligand binding that can be detected with conformation dependent monoclonal antibodies (mAbs). By using such conformation-dependent mAbs, we could demonstrate that activation of integrin ␣ IIb ␤ 3 is not only sufficient, but also a prerequisite fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 56 publications
1
34
0
Order By: Relevance
“…4,5 Our evidence supports the existence of a functional synergy between ␣2␤1 and GPVI, but not simply to the effect that GPVI provides primary signals subsequently amplified by ␣2␤1. 31,37 Not only did we find that ␣2␤1 can signal independently of GPVI or ␣IIb␤3 (GPIIb-IIIa), 38 as clearly confirmed by the induction of ␣-like Ca 2ϩ peaks on selective ␣2␤1 ligation by the GFOGER peptide, but also that GPVI functions are facilitated by preceding ␣-like Ca 2ϩ elevations dependent on ␣2␤1 engagement. Such conclusions do not exclude the possibility that ␣2␤1 ligand-binding affinity is further enhanced after GPVI interaction with collagen and/or ␣IIb␤3 activation.…”
Section: Discussionsupporting
confidence: 60%
“…4,5 Our evidence supports the existence of a functional synergy between ␣2␤1 and GPVI, but not simply to the effect that GPVI provides primary signals subsequently amplified by ␣2␤1. 31,37 Not only did we find that ␣2␤1 can signal independently of GPVI or ␣IIb␤3 (GPIIb-IIIa), 38 as clearly confirmed by the induction of ␣-like Ca 2ϩ peaks on selective ␣2␤1 ligation by the GFOGER peptide, but also that GPVI functions are facilitated by preceding ␣-like Ca 2ϩ elevations dependent on ␣2␤1 engagement. Such conclusions do not exclude the possibility that ␣2␤1 ligand-binding affinity is further enhanced after GPVI interaction with collagen and/or ␣IIb␤3 activation.…”
Section: Discussionsupporting
confidence: 60%
“…84 A recent study that used an antibody that recognizes activation-induced conformational changes in ␣2␤1 suggested that the activation of this integrin is dependent on the previous activation of ␣IIb␤3. 85 However, the underlying mechanisms have not been identified and it remains to be determined whether the detected conformational changes indeed reflect "activation" of the integrin.…”
Section: Integrin ␣2␤1mentioning
confidence: 99%
“…33,34 Like other integrins, conformational activation of α2β1 increases its affinity for collagen, and seems to require inside-out signaling events that might be driven by engagement of GP VI with collagen 23 and/or by activation of αIIbβ3. 35 Recent findings indicate that the mechanism of activation of α2β1 is similar to that of other integrins and involve unclasping of the corresponding transmembane domain upon interaction of the α1 cytoplasmic tail with talin and kindlin-3. 36 Moreover, collagen binding to α2β1 also triggers outsidein signaling resembling that induced by GP VI, 23 that reinforces platelet activation.…”
Section: Initiation Phasementioning
confidence: 99%